Information technology teachers' perception of implementing the National Education Technology Standards - Walton-Todd, Linda B., author; Davies, Timothy G., advisor; Morgan, George A., committee member; Lewis, Chance W., committee member; Shears, Jeffrey, committee member (Colorado State University. Libraries, 2006)
Business education teachers were given a new charge in the early 1900s—to teach new technology—as a result of which the business education teachers became the information technology teachers. The teachers were given optional training. Some accepted the new technology, while others were frightened of learning it and using the equipment. Then national technology skill standards were developed to insure that all teachers were integrating technology into their subject areas. The business teachers now were looked to for assistance in training other teachers about technology. This non-experimental study addresses how many of the information technology teachers in the Chicago Public Schools system perceive they are addressing the national technology skill standards. The teachers were surveyed concerning their technology preparation, skills, experience, and general background in delivering the National Education Technology Standards (NETS), National Standards for Business Education (NSBE), and Secretary's Commission on Achieving Necessary Skills (SCANS). The study found that few teachers were Microsoft Office Specialist (MOS) certified. Half of the respondents had taken a refresher technology course within the year. Sixty percent of them perceived they were prepared to implement national technology skill competencies. Out of the nine reporting areas, the teachers' strongest confidence for implementation was word processing; and the weakest was HTML and web page design. All but one of the gender variable comparisons was non-significant as it relates to preparation and skills in implementing technology competencies; females overall had more years of teaching. Most of the teachers were aware of the standards, but less than 30% of the teachers' had formal training, and 80% requested formal training. The teachers enumerated the staff development of HTML/Web Page Development, NETS, SCANS, and NSBE because they would enhance their delivery of national technology skill standards competencies.
Keywords: teacher education